ABIDE: An Accurate Predictive Model of Liver Decompensation in Patients With Nonalcoholic Fatty Liver‐Related Cirrhosis. Issue 6 (19th April 2021) - Calzadilla‐Bertot, Luis; Vilar‐Gomez, Eduardo; Wong, Vincent Wai‐Sun; Romero‐Gomez, Manuel; Aller‐de la Fuente, Rocio; Wong, Grace Lai‐Hung; Castellanos, Marlen; Eslam, Mohammed; Desai, Archita P.; Jeffrey, Gary P.; George, Jacob; Chalasani, Naga; et al.
Abstract : Background and Aims: Nonalcoholic fatty liver disease (NAFLD) is an increasingly important cause of liver cirrhosis and subsequent complications. We retrospectively developed and validated a model to predict hepatic decompensation in patients with NAFLD and cirrhosis and compared this with currently available models. Approach and Results: Baseline variables from an international cohort of 299 patients with biopsy‐proven NAFLD with compensated cirrhosis were examined to construct a model using competing risk multivariate regression and Akaike/Bayesian information criteria. Validation was performed in 244 patients with biopsy‐proven NAFLD cirrhosis from the United States. Prognostic accuracy was compared with the NAFLD fibrosis score (NFS), fibrosis‐4 (FIB‐4), Model for End‐Stage Liver Disease (MELD), Child‐Turcotte‐Pugh (CTP), and albumin‐bilirubin (ALBI)‐FIB‐4 score using time‐dependent area under the curve (tAUC) analysis. During a median follow‐up of 5.6 years (range 2.4‐14.1) and 5.4 years (range 1.5‐13.8), hepatic decompensation occurred in 81 and 132 patients in the derivation and validation cohorts, respectively. In the derivation cohort, independent predictors of hepatic decompensation (Aspartate aminotransferase/alanine aminotransferase ratio, Bilirubin, International normalized ratio, type 2 Diabetes, and Es ophageal varices) were combined into the ABIDE model. Patients with a score ≥4.1 compared with those with a score <4.1 had a higher risk of decompensation (subhazard ratio, 6.7; 95% confidence interval [CI], 4.0‐11.2; P < 0.001), a greater 5‐year cumulative incidence (37% vs. 6%, P < 0.001), and shorter mean duration to decompensation (3.8 vs 6.7 years, P < 0.001). The accuracy of the ABIDE model at 5 years was good in the derivation (tAUC, 0.80; 95% CI, 0.73‐0.84) and validation cohorts (0.78; 95% CI, 0.74‐0.81) and was significantly more accurate than the NFS (0.72), FIB‐4 (0.74), MELD (0.69), CTP (0.72), and ALBI‐FIB‐4 (0.73) (all P < 0.001). Conclusions: In patients with NAFLD and compensated cirrhosis, ABIDE, a predictive model of routine clinical measures, predicts future hepatic decompensation.